Building locally relevant ethics curricula for nursing education in Botswana. (December 2014) - Barchi, F.; Kasimatis Singleton, M.; Magama, M.; Shaibu, S.
Abstract : Aim: The goal of this multi‐institutional collaboration was to develop an innovative, locally relevant ethics curriculum for nurses in Botswana. Background: Nurses in Botswana face ethical challenges that are compounded by lack of resources, pressures to handle tasks beyond training or professional levels, workplace stress and professional isolation. Capacity to teach nursing ethics in the classroom and in professional practice settings has been limited. Methods: A pilot curriculum, including cases set in local contexts, was tested with nursing faculty in Botswana in 2012. Results: Thirty‐three per cent of the faculty members indicated they would be more comfortable teaching ethics. A substantial number of faculty members were more likely to introduce the International Council of Nurses Code of Ethics in teaching, practice and mentoring as a result of the training. Based on evaluation data, curricular materials were developed using the Code and the regulatory requirements for nursing practice in Botswana. A web‐based repository of sample lectures, discussion cases and evaluation rubrics was created to support the use of the materials. Discussion: A new master degree course, N ursing   E thics in   P ractice, has been proposed for fall 2015 at the University of Botswana. The modular nature of the materials and the availability of cases set within the context of clinical nurse practice in Botswana make them readily adaptable to various student academic levels and continuing professional development programmes. Conclusion: The ICN Code of Ethics for Nursing is a valuable teaching tool in developing countries when taught using locally relevant case materials and problem‐based teaching methods. Implications for Nursing: The approach used in the development of a locally relevant nursing ethics curriculum in Botswana can serve as a model for nursing education and continuing professional development programmes in other sub‐Saharan African countries to enhance use of the ICN Code of Ethics in nursing practice.